Management of Guidance and Counseling Programs Based on Spiritual Values at SMA Negeri 1 Way Khilau Pesawaran Lampung - Khairiah, Khairiah; Hendrowati, Tri Yuni; Aswad, Fatqul Hajar (Lembaga Riset Mutiara Akbar, 2025)
Spiritual-based character education is increasingly important in addressing the moral challenges of the younger generation in the era of globalization. This study aims to analyze the management of a spiritual-based guidance and counseling (BK) program at SMA Negeri 1 Way Khilau, Pesawaran Regency. The study used a descriptive qualitative method with data collection techniques through interviews, observation, documentation, and questionnaires. Research informants included the principal, BK teachers, religious teachers, and students. The results showed that the BK program management was carried out through four main stages: planning, organizing, implementing, and evaluating. This program integrated counseling services with spiritual habits such as Dhuha prayer, morning sermons, and Islamic mentoring. Program evaluation indicated increased discipline, student involvement in religious activities, and strengthening of religious character. The program's success was supported by a religious school culture and the principal's leadership, although obstacles remained such as a limited number of BK teachers and low parental involvement. This study confirms that the integration of spiritual values in BK services is an effective strategy for shaping student character and can serve as a model of good practice for other schools.